Relationship between throwing velocity, muscle power, and bar velocity during bench press in elite handball players - Marques, M. C.; van den Tillaar, R.; Vescovi, J. D.; Gonzalez-Badillo, J. J. (International Journal of Sports Physiology and Performance, 2007)
The purpose of this study was to examine the relationship between ball-throwing velocity during a 3-step running throw and dynamic strength, power, and bar velocity during a concentric-only bench-press exercise in team-handball players. Methods: Fourteen elite senior male team-handball players volunteered to participate. Each volunteer had power and bar velocity measured during a concentric-only bench-press test with 26, 36, and 46 kg, as well as having 1repetition-maximum (1-RMBP) strength determined. Ball-throwing velocity was evaluated with a standard 3-step running throw using a radar gun. Results: Ball-throwing velocity was related to the absolute load lifted during the 1-RMBP (r = .637, P = .014), peak power using 36 kg (r = .586, P = .028) and 46 kg (r = .582, P = .029), and peak bar velocity using 26 kg (r = .563, P = .036) and 36 kg (r = .625, P = .017). Conclusions: The results indicate that throwing velocity of elite team-handball players is related to maximal dynamic strength, peak power, and peak bar velocity. Thus, a training regimen designed to improve ball-throwing velocity in elite male team-handball players should include exercises that are aimed at increasing both strength and power in the upper body.